Analisis Efektivitas Biaya Penggunaan Antibiotik Pasien Pneumonia Pada Balita di Rumah Sakit Umum Daerah Wangaya - NI KOMANG WIJA KUSUMA WATI (Bali International University, 2021)
ABSTRACT Clinically pneumonia is defined as a inflammation caused by microorganisms (bacteria, viruss, fungi, parasites). Pneumonia that often occurs and is serious is community-acquired pneumonia (CAP). Antibiotics are the mainstay of therapy for CAP which is caused by bacteria. The purpose of this study was to determine the cost-effectiveness analysis of the use of antibiotics for pneumonia patients in children under five year at Wangaya Regional General Hospital. The method in this study is a cross-sectional of patient medical records in 2019. The data collection method in this study is observation. Subjects used in this study were patients diagnosed with pneumonia community acquired pneumonia CAP in children under five year at the Wangaya Regional General Hospital, with antibiotic therapy of ceftriaxone and cefotaxime. The results of this study are that there are differences that significant P 0,05 on mean total cost of treatment between ceftriaxone treatment arm compared to cefotaxime. For effectiveness there was no significant difference P 0,05 in the effectiveness of treatment between the ceftriaxone group and the cefotaxime group. The effectiveness of treatment was seen from the length of stay, duration of antibiotic use and decreased respiration rate. The cefotaxime group was more cost effective than the ceftriaxone group. It is necessary to carry out similar studies in different locations in order to know the comparison of the cost-effectiveness of antibiotic therapy in other areas, thereby increasing reference in the selection of antibiotics that are cost-effective and therapeutic effectiveness. Keywords: Cost-effectiveness analysis, Pneumonia, Antibiotics, Children Under Five Year